O brincar na educação infantil em tempos de pandemia: concepções docentes - Abreu, Ana Katrine de (Brasil, 2024)
The present work of Conclusion of Course had as main objective to analyze how the playful activities were developed by teachers mediators of the project Educational Radio School for students of Early Childhood Education; Identify which methodological strategies were used to bring quality education to children via radio; To analyze how the playful pedagogical practice was developed by mediating teachers of the educational project Radio School: in the waves of knowledge whether these practices contributed to the development of the skills and competencies of children in Education. Among the theoretical framework, we highlight: Kishimoto (2002), Alves (2010), Piaget (1994) and others who discuss and study about the cognitive development of children and the importance of play for their full development, and in official documents that govern Early Childhood Education, such as BNCC (2018), LDB (1996), ECA (1990) and DCNEI (2009). The research was carried out at the Municipal School of Early Childhood Education Frei Benigno Falchi and with the Manager of Early Childhood Education of SEMED and three (3) teachers of Early Childhood Education who acted as mediators in the project, one from Maternal III, one from Pre I, and one from Pre II. In this way this research is characterized as a field research of qualitative approach, of the exploratory type, the techniques used for data collection were bibliographic study, documentary analysis and questionnaire, the method applied was that of phenomenological research which provided conditions for obtaining the necessary information on the theme addressed in this work. The research showed that the use of Radio as a mass communication technology guaranteed the rights and objectives of learning in Early Childhood Education by the participation of children through audio, videos, text message and telephone calls, activities carried out at home with the help of the family as well as the participation of children during the mediation of classes on the Radio and the use of the handout, which contributed to their learning and development.